Efficacy of fungicides against brown spot of pear in Argentina - Tudela, Marisa Andrea Aluminé; Lutz, María Cecilia; Giménez, Gustavo Nestor; Del Brio, Dolores; Di Masi, Susana Noemi; Pose, Gabriela Noemí; Edwards Molina, Juan Pablo (Elsevier, 2023)
Brown spot of pear (BSP), a fungal disease of importance in Europe, has been recently detected for the first time in pear orchards in the Alto Valle of Río Negro (Patagonia), Argentina, South America. The disease is caused by Stemphylium vesicarium and its main symptoms are lesions in fruits and leaves. To assess counteracting measures against BSP, we tested the efficacy of fungicides by means of in vitro assessment of mycelial growth and spore germination of native S. vesicarium strains, and in vivo preventive and curative treatments in pear fruit ’D’Anjou’ var. The fungicides were chosen according to their commercial availability and registration in pear crops and included: pyraclostrobin + boscalid (Bellis®); ziram (Ziram®); captan (Merpan®); and Melaleuca alternifolia extract (Timorex®). In addition, the efficacy of Bellis® and Ziram® was determined through in-field assays. Bellis® presented the lowest EC50 values in germination and mycelial growth tests. Ziram® and Merpan® were also very effective in inhibiting germination. Timorex® did not achieve satisfactory effectiveness in in vitro trials, nor in bioassays after preventive and curative treatments. Bioassay results showed that preventive mea sures using Bellis®, Ziram®, or Merpan® were effective in reducing disease severity and suggested that BSP could be controlled by adequate selection of spraying time.